To Enhance Light Extraction for Organic Light-Emitting Diodes by Body Modification of Substrate - Jun Wang; Chong Wang; Yadong Jiang (International Journal of Photoenergy)
A facile approach of body modification on substrate is introduced to enhance the light extraction for organic devices. The lateral metal reflective film (LMRF) was coated on side of substrate and microlens array (MLA) was fabricated on forward surface of substrate. The two methods of improving light output are simulated and optimized to form body modification. The metal thin film was evaporated on the side of reversal trapezoid shape substrate to form LMRF layer and the MLA with semicircle shape was fabricated on the substrate using normal photolithography process. The external quantum efficiency of fabricated organic device with body modification is ~1.8 times higher than the device with normal substrate.